Artificial nest predation by brown howler monkeys (Alouatta guariba clamitans) - Bicca-Marques, Júlio César; Silveira, Ivana Regina Rodrigues Irace; de Souza Martins, Leonel; Rabelo, Rafael Magalhães (European journal of wildlife research, 2014)
Howler monkeys (Alouatta spp.) have long been considered strongly vegetarian primates. Their occasional ingestion of invertebrates has largely been interpreted as unintentional. Recent observations of the consumption of bird eggs by Alouatta caraya living in small and resource-impoverished habitat patches in the state of Rio Grande do Sul (RS), Brazil help to confirm that such behavior by howler monkeys is at times intentional. We report the findings of an experimental study on artificial nest predation by free-ranging Alouatta guariba clamitans in RS and third-party unpublished observations of intentional feeding on animal matter by Alouatta arctoidea in Venezuela and Alouatta palliata in Mexico. A nest station composed of ten artificial nests baited daily with two quail eggs each was placed at six study sites. Each site was monitored from dawn to dusk during 10–12 consecutive days. Individuals (juvenile males and an adult female) from two of the six study groups inspected the nests and ate eggs once. Study subjects from these two groups were the only ones to be supplemented with food (basically fruit) by local inhabitants, a habit that may have decreased their level of neophobia and facilitated their visit to the artificial nests. We suggest that faunivory is an opportunistic and infrequent, but intentional howler monkey feeding behavior.